Students’ Perceptions of Acoustic Comfort in Traditional and Flexible Learning Environments: A Study in Chile - Ipinza-Olatte, C (Institute of Physics, 2023)
The acoustic quality of educational spaces has an important impact on well-being and occupant performance. This study investigates noise perception and hearing ability among primary students in traditional learning environments (TLE) and flexible learning environments (FLE). A survey was conducted in Santiago de Chile, involving 21 teachers and 315 children from 13 schools, to gather responses on acoustic comfort. Additionally, a checklist was used to inspect the physical spaces. The analysis of students responses revealed that self-reported complaints related to indoor environmental quality (IEQ) predominantly focused on noise discomfort in both types of learning environments. A significant relationship was found between the type of space and children’s perception of noise from their peers. Although students in TLE reported greater annoyance with noise, those in FLE experienced slightly more listening problems. Interestingly, in FLE, students with an occupancy density greater than 2.1 m2 per student did not feel bothered by the noise produced by their classmates speaking. Although further research is needed, these findings highlight the crucial role of acoustic conditions in ensuring the comfort and hearing abilities of young students. Adequate acoustic treatment and enough space per student are important to mitigate potential indoor noise issues. © 2023 Institute of Physics Publishing. All rights reserved.